DLP printed β-tricalcium phosphate functionalized ceramic scaffolds promoted angiogenesis and osteogenesis in long bone defects. Issue 18 (15th September 2022) - Bi, Gangyuan; Mo, Lina; Liu, Sa; Zhong, Xiupeng; Yang, Junzhong; Yuan, Zhongrun; Chen, Shenggui; Ren, Li
Abstract: Nowadays, the repair of long bone defects remains a clinical challenge mainly due to poor oxygen and nutrients delivery. In this study, β-tricalcium phosphate (β-TCP) porous ceramic scaffolds were prepared by digital light processing (DLP) and gradient sintering process. The functionalization of scaffolds was achieved by loading hyaluronic acid-dopamine (HA-DA) coating or sphingosine 1-phosphate/hyaluronic acid-dopamine (S1P/HA-DA) coating, which solved the problem of oxygen and nutrients delivery to a certain extent by promoting blood vessels growth. Cytocompatibility assay, qRT-PCR, Alkaline phosphatase (ALP) staining and quantitative analysis demonstrated that the S1P/HA-DA/TCP scaffolds significantly promoted the proliferation and osteogenic differentiation of mouse bone marrow mesenchymal stem cells (mBMSCs). Long bone defects (22 mm), rarely reported in previous studies, were constructed on the radius of rabbits. Animal experiments showed excellent early angiogenesis and bone repair in HA-DA/TCP and S1P/HA-DA/TCP groups. In particular, the S1P/HA-DA/TCP scaffolds enhanced bone regeneration and osseointegration. Overall, these functionalized scaffolds had an effective repair on long bone defects that would have great potential for clinical applications. Graphical abstract: Image 1